Restrictive practices in English schools: an interpretative phenomenological analysis of parental lived experience - Christie, Carly; Harding, Emma (Frontiers in Education, 2025)
This paper presents an exploration of the lived experiences of parents whose children have been exposed to the use of restrictive practices (RPs) in schools in England. The research utilized Interpretative Phenomenological Analysis to provide a deep and interpretative understanding. Semi-structured interviews were used to elicit the lived experiences of five parents, whose children had experienced a range of RPs in school. The analysis produced three major themes which centered around the power imbalances, the emotional labor and the practical consequences of RP use. The findings are discussed in the context of neoliberalism, and key implications for practice, research, and policy are reflected.